Tajribadagi Sigirlarning Yelin Xususiyatlari Va Sut Mahsuldorligining Yelin Shakllariga Bog‘Liqligi - Xoljigitov Asqar Marifjonovich; Eshdavlatov Orif Zokirovich (Open Academia, 2023)
When assessing the degree of adaptation of cow Yelin to modern milking equipment in livestock herds, it will be of particular importance to assess the morphological and functional characteristics of the Yelin, depending on the dairy productivity of cows.
Keywords: sigir; yelin, sut; chorva mollari